Peran pustakawan di Perpustakaan Universitas Indonesia dalam upaya preservasi digital pada koleksi e-local content - Nabila Aulia; Tamara Adriani Salim (Perpustakaan Universitas Gadjah Mada, 2023)
Introduction. Digital preservation is the process of maintaining collections in digital format to ensure access, usability, and long-term durability for users. This research aims to identify the role of librarians and library staff in carrying out digital preservation activities on e-local content collections at the Universitas Indonesia Library. Data Collection Methods. The method used was qualitative research with a case study type. Data collection techniques were conducted through interviews, observations, and document study. Data Analysis. The data analysis technique used was data reduction, data presentation, data validation, and conclusion drawing. Results and Discussion. The role of librarian in the digital preservation of e-local content or UI-ana collections are collection preservation agents, guarantors of access to information, defenders of preservation policies, guardians of adaptation to technology, and leaders in networking between staff and managers. Conclusion. The role implemented by library staff is quite good. However, software and hardware updates are needed, and special policies can be made so that digital preservation of e-local content collections can run optimally.